Psychosocial Characteristics of Children with and Without Toileting Dysfunction - (:unkn) unknown (My University, 2019)
Toilet training is a stressful time for parents and families; however, pediatric providers are often uncertain of how to guide parents through this period because of limited systematic research in this area. The current study investigated the role of timing and method of toilet training, use of physician and community resources, and parent and child psychosocial variables to better understand normative toilet training and clarify the role of family, parent, and child characteristics in the toilet training process. The literature regarding early childhood development and normative toileting was reviewed, followed by a discussion of voiding dysfunction and relevant psychosocial and cultural patterns. Participants included 437 community parents (77% female, 82% White, 69% married) of children (48% female) between the ages of two- and six-years-old. A subclinical sample (n=27) and matched controls who did not experience toilet training challenges were identified from within the larger community sample. Data were gathered through an online retrospective survey including measures of demographics, family functioning, child behavior, child temperament, parenting style, parent stress, and open-ended questions about toilet training decisions and resources. Qualitative results indicated that parents used numerous methods of toilet training and half of parents did not consult their child’s primary care provider during the process. Most children were toilet trained by three-years-old. Five latent groups of children were identified in the current sample. Classes differed primarily along child behavior symptoms, temperamental activity, negative parenting behaviors, household conflict, and reported use of child-centered toilet training. The subclinical sample had significantly higher ADHD symptoms and were described as slightly more emotionally labile than the matched non-clinical group. The results of this study indicate that family-system variables likely influence how children are toilet trained. These findings support further consideration of the recommendations provided to parents prior to beginning their child’s toilet training and highlight the need for additional attention to the family system during this process.
Keywords: Child behavior; Family functioning; Latent variable mixture modeling; Parenting; Toileting